Marital Adjustment and Prenatal Breastfeeding Efficacy of First Time Mothers in A Low-Income Community in The Philippines - Artemio Jr Morado Gonzales (Universitas Airlangga, 2020)
Introduction: All women should be offered support to breastfeed their babies to increase the duration and exclusivity of breastfeeding. This study aims to assess the level of marital satisfaction and its influence to prenatal breastfeeding self-efficacy in   first time mothers during late pregnancy. Methods: A descriptive correlational was conducted among 128 simple randomized prim gravid women who agreed to participate and had prenatal care check-up in the health center at the time of data gathering. The instruments used were 15-item Marital Adjustment Test (MAT) to measure marital adjustment and 14-item Breastfeeding Self efficacy Scale-Short Form (BSES-SF) as a measure of breastfeeding self-efficacy. Pearson's correlation coefficient was utilized to test the relationships between the sample's marital adjustment scores to correlate with BFSE of the respondents. Fisher's t test was utilized to determine the significance of correlations. A p-value of equal to or less than .05 was considered statistically significant. Results: The study revealed that the sampled mothers have a high level of marital adjustment score (112.05± 21.83). Prenatal mothers responded in the study were highly confident and have high self-efficacy in breastfeeding first child currently bearing (4.55±.51). Lastly, it was found that there is no significant correlation between marital adjustment and prenatal breastfeeding self-efficacy (β=-.052, p-value=.280). Conclusion: It was found  that there is a high level of marital adjustment and breastfeeding self-efficacy among sampled mothers. However, there is no significant correlation between marital adjustment and prenatal breastfeeding self-efficacy. The study suggests incorporating co-parenting intervention involving father's involvement and assistance with breastfeeding when creating interventions in breastfeeding.